PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN, SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Kasus pada Kantor Pelayanan Pajak Pratama Magelang) - Irfan Kurniawan (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study attempts to test influence modernization tax administration systems, and sanctions against compliance taxation taxpayers individual. The research was conducted in the taxoffice pratama magelang. The data used the research is primary data obtained by thequestionnaire, and in the sample used in research has reached 83. A method of the sample usingaccidental sampling and analysis techniques the data used was analysis techniques multipleregression. The result of this research showed that modernization tax administration in partial have hada positive impact and significant impact on compliance taxpayers.Sanctions taxation in partial havehad a positive impact and significant impact on compliance taxpayers.Simultaneouslymodernization tax administration systems, and sanctions taxation have had a positive impact andsignificant impact on compliance taxpayer with value adjusted r square of 42,8 %.